Signal detection of Rhabdomyolysis and death for galantamine: a pharmacovigilance study - Karmaker, Swastika (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2023.